Associations between self-reported fitness and self-rated health, life-satisfaction and health-related quality of life among adolescents - Adilson Marques; Jorge Mota; Tânia Gaspar; Margarida Gaspar de Matos (Elsevier, 2017)
Background/objective: In recent years, there has been an increased interest in the associations between physical fitness (PF) and psychosocial aspects of health. This study aimed to analyse the associations between self-reported PF and self-rated health (SRH), life-satisfaction (LS), and quality of life (QoL). Methods: This is a cross-sectional study of 3554 adolescents (1652 boys), aged 13-18, from the HBSC Portuguese survey. PF, health, LS and OoL were self-rated. Results: SRH, LS, and health-related OoL (HRQoL) were significantly and positively correlated with all PF components. From regression model, overall fitness was significantly related with SRH (boys: β = 0.18, p < 0.001; girls: β = 0.16, p < 0.001), LS (boys: β = 0.36, p < 0.001; girls: β = 0.43, p < 0.001), and HRQoL (boys: β = 2.26, p < 0.001; girls: β = 2.54, p < 0.001). Cardiorespiratory fitness was also positively and significantly related with SRH (boys: β = 0.17, p < 0.001; girls: β = 0.11, p < 0.001), LS (boys: β = 0.13, p < 0.05; girls: β = 0.31, p < 0.001), and HRQoL (boys: β = 1.74, p < 0.001; girls: β = 1.57, p < 0.001). Conclusion: These findings suggest that perceived PF is associated with a better SRH, LS, and perceived HRQoL. A few implications regarding public policies were highlighted.